Does the F-score improve the performance of different value investment strategies in Europe? - Tikkanen, Jarno; Äijö, Janne (Palgrave Macmillan, 2018)
This study examines whether the performance of 8 different value investment strategies can be improved with 9 Piotroski’s (J Account Res 38:1–41, 2000) F-score screening method for the European stock markets. Our aim is to investigate the ability of the screening method to distinguish between winners and losers among several value investment strategies that use different financial ratios to form portfolios, such as B/M, E/M, D/M, and EBITDA/EV ratios. The results of the study provide compelling evidence that the F-score screening method significantly improves the performance of all investigated investment strategies. The results regarding the superior performance of the high F-score portfolios are robust across investment strategies, various performance mea21 sures and risk-adjustment methods. The results are useful for individual investors and professional portfolio managers.
Keywords: Anomalies; F-score; Portfolio management; Portfolio performance; Value investment strategy; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|